VOCABULARY IN AGRIBUSINESS: CONCORDANCE AS A CLASS ACTIVITY - Bernardon, Maura (Revista Expectativa, 2000)
This article is related to ESP, vocabulary teaching, and computer corpus data. These three elements together can lead to new methodologies in language teaching, for example, computer-generated concordances that are very helpful for grammar and vocabulary teaching (BUTLER, 1998). Based on discourse analysis, genre theories, and corpus linguistics teacher have new ways of vocabulary practices, using authentic and contextualized data. Moreover, working with computer corpus data gives a great support to teachers in terms of use of language and with more specialized vocabulary. I suggest also that this proposal can also be helpful in the development of reading materials for classes of ESP classes.